PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KOTA TERNATE - Ruslan A Kamis; Wariani Lainta (Jurnal Manajemen Sinergi, 2017)
This study aims to determine the Effects of Employee Motivation on Performance In Ternate City Department of Transportation, to determine the effect of job satisfaction Against Employee Performance In Ternate City Department of Transportation. Model analysis of the data used in this study is multiple regression analysis (multiple regression analysis). Multiple regression analysis was used to analyze the effect of independent variables consisting of motivation (X1), and job satisfaction (X2), the dependent variable is the performance of an employee (Y). The reason to use this model because the authors wanted to determine how much influence motivation and job satisfaction on the performance of employees at the Department of Transportation of Ternate. Based on statistical tests of motivation and job satisfaction affects employee performance, so the hypothesis is built within the framework of this study is acceptable. The results of this study found that both the proposed research variables in this study can enhance the performance of the employees, this can be seen in the results of multiple regression test simultaneously give effect to the performance of employees. Motivation and job satisfaction perceived by the Department of Transportation Employee of Ternate by the leader of an indicator that encourages employees to carry out the duties and functions that have been planned